Predictors of hope in Iranian patients undergoing hemodialysis - Sakineh Moghaddam Zeabadi; Mehdi Ranjbaran; Farnoosh Rashvand; Akram Rostampourromdasht; Seyedehzahra Hosseinigolafshani (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Patients undergoing hemodialysis (HD) are more vulnerable to mental, physical and spiritual disorders. These disorders may have a significant impact on their treatment process and quality of life (QoL). Given the importance of some experiences in these individuals, such as daily spiritual experiences and life expectancy, evaluating their predictive role seems necessary. Objectives: This study was conducted to determine the role of daily spiritual experiences and some demographic variables in predicting the level of hope among HD patients. Patients and Methods: In this cross-sectional study, the predictive role of daily spiritual experiences and some demographic variables in the level of hope in 262 HD patients were evaluated. The demographic variables checklist, the Daily Spiritual Experiences Scale (DSES), and the Adult Hope Scale were employed for data collection. Results: Analysis with multiple linear regression showed that the variables of gender, level of education, duration of diagnosis of renal failure, number of HD per week and daily spiritual experiences predicted 31% of the level of hope changes in HD patients. Conclusion: Nurses and provincial health care providers can help HD patients to promote their spiritual wellbeing and hope. This can be achieved by applying a holistic care approach as well as emphasizing the spiritual aspect of care and its predictive demographic variables.